Sosialisasi Zero Waste Living Margo Mulyo “Menciptakan Lingkungan Sekolah Bersih dan Sehat” - Waladdin Panggabean; Gessy Rantrove Nainggolan; Nur Hafidah Rahman; Micky Andhreanto; Graciella Manope; Dewi Sekar Arningtias; Muhammad Rafli; Thalia Fitri Salsabila; Wita Saulina; Alfa Rizky Ramadhan; Syara Arini Putri (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Waste management in the school environment remains a challenge in creating a clean and healthy learning environment. The lack of students' understanding of waste management and the health impacts of littering behavior is the background of this activity. The